DEVELOPMENT OF THE SYSTEM OF BALANCED SCORECARD FOR ENTERPRISES OF THE PETROCHEMICAL COMPLEX TATNEFT - Karamyshev, Anton N.; Gabdullina, Gulsina K.; Yakovlev, Anatoly Ye. (Gênero & Direito, 2019)
Regional policy in the field of law-making in support of innovation, investment, improvement of interregional and international relations, on the one hand, and implementation of the provisions of the antimonopoly legislation, replenishment of the budget, development of economic, financial, transport and other infrastructure of the region, on the other hand, discloses the content of favourable, and constraining the development of corporate activities conditions that determine the purpose and planned value of indicators of the corporation functioning. Establishment of economic targets from the scientific and practical point of view is only one side of the management function, it is important to organize the accounting, analysis and evaluation of the effectiveness of achieving the goals of the corporation, the results of which serve as the information base for making managerial decisions and adjusting planned activities.Indicators of the effect and efficiency of managing corporations are the subjects of many discussions. At the same time, it is important to understand that attention should be drawn not as much to the results obtained, as to the conditions and factors that determined them. The analysis of cause-effect relationships allows modern corporations to build a system of dependencies, to adjust their development strategy taking into account their territorial affiliation and to apply modern tools for matrix analysis and planning, to which the system of balanced scorecard of Norton and Kaplan can be related.